Synthetic analogues of migrastatin that inhibit mammary tumor metastasis in mice - Shan, Dandan (National Academy of Sciences, 2005)
Tumor metastasis is the most common cause of death in cancer patients. Here, we show that two, fully synthetic migrastatin analogues, core macroketone and core macrolactam, are potent inhibitors of metastasis in a murine breast tumor model. Administration of these readily accessible compounds nearly completely inhibits lung metastasis of highly metastatic mammary carcinoma cells. Treatment of tumor cells with core macroketone and core macrolactam blocks Rac activation, lamellipodia formation, and cell migration, suggesting that these chemical compounds interfere with the invasion step of the metastatic process. These compounds also inhibit the migration of human metastatic breast cancer cells, prostate cancer cells, and colon cancer cells but not normal mammary-gland epithelial cells, fibroblasts, and leukocytes. These data demonstrate that the macroketone and macrolactam core structures are specific small-molecule inhibitors of tumor metastasis. These compounds or their analogues could potentially be used in cancer-therapy strategies.